The Relationship between Ethics and the Legal Profession Code of Ethics in Law Enforcement Efforts in Indonesia - Nanda Dwi Rizkia; Hardi Fardiansyah (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
Professional ethics is a set of standards established and accepted by specific professional groups as guidance on how to build and ensure the quality of their profession for its members. This research focuses on the ethics of police, prosecutors, judges, lawyers, and notaries. All of these fall under legal professional ethics, also known as special legal ethics. The research method employs normative legal research and conducts a review of regulations through a comparative approach. The research findings indicate that the relationship between ethics and the legal profession forms an institutional framework that carries out a series of crucial functions in social roles, especially in the development of science, humanities, and the field of education. During the implementation process, these professions do not always operate automatically based on beliefs in the importance of their functions but can be significantly influenced by various social power interactions. Ethics in the legal profession plays a crucial role in achieving fair law enforcement. Therefore, ethics in the legal profession (professional code of ethics) is a highly important part in regulating the behavior of legal practitioners, representing fair law enforcement